THE EFFECT OF SUBSTITUTION AND COMBINATIONOF FEED ON THE GROWTH AND SURVIVAL RATEOF SHEAT FISHLARVAE (Ompokrhadinurus Ng.) - Mona Yuristi; Netti Aryani; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe research was conducted on 24 November 2019-2 January 2020at Fish Breeding and Breeding Laboratory, Faculty of Fisheries and Marine, University of Riau. Aims to determine the effect of the best type of feed (Tubifexsp., Water Fleas or Artificial Feed) best to replace initial feed (Artemiasp.) and best combination of feed on growth and survival rate of Sheat fish larvae. The researchusingCompletely Randomized Design (CRD). The treatment used P1= Artemia sp. (age 7-17 days) + Tubifex sp. (age 17-27 days)+Artificial Feed (age 27-37 days)+Water fleas (age 37-47 days), P2= Artemia sp. (age 7-17 days)+Artificial Feed (age 17-27 days)+Water fleas (age 27-37 days)+Tubifexsp.(age 37-47 days), P3= Artemia sp. (age 7-17 days)+Artificial Feed (age 17-27 days)+Tubifex sp. (age 27-37 days)+Water fleas (age 37-47 days), P4= Artemia sp. (age 7-17 days)+Tubifex sp. (age 17-27 days)+Water fleas (age 27-37 days)+Artificial feed (age 37-47 days), P5 = Artemia sp. (age 7-17 days)+Water fleas (age 17-27 days)+Tubifex sp. (age 27-37 days)+Artificial Feed (age 37-47 days), P6= Artemiasp. (age 7-17 days)+Water fleas (age 17-27 days)+Artificial Feed (age 27-37 days)+Tubifexsp. (age 37-47 days). From the results of research the best feed to substitusionArtemia sp. is Tubifexsp. produce weight growth 0.6340 g,length growth 4.1 cm,daily weight growth39,37%/day and survival rate 96,79%. In the combination treatment of feed did not have a real effect on absolute weight growth, daily weight growth and survival rate but has a real effect onabsolute length growth of8,1 cm on treatment P4 (Artemiasp.+Tubifexsp.+Water Fleas+Artificial Feed).Water quality during the research temperatures 26-270C, pH 5,2-6,5 and DO 3,6-4,67 ppm.Keywords: Artemiasp., Tubifexsp., Ompok rhadinurus Ng.